Survival and Growth of Chestnut Backcross Seeds and Seedlings on Surface Mines. Issue 3 (1st May 2013) - Skousen, J.; Cook, T.; Wilson‐Kokes, L.; Pena‐Yewtukhiw, E.
Abstract : Some scientists consider the loss of the American chestnut from forests in the eastern United States as one of the greatest forest ecological disasters in the 20th century. The American Chestnut Foundation has been attempting to restore chestnut by backcrossing blight‐resistant Chinese chestnut to American chestnut and selecting those strains with blight resistance. Third‐generation backcross seeds and seedlings have been produced and planted by researchers. Surface‐mined lands provide a land base where these backcross chestnut seedlings may be introduced back into forests. In 2008, seeds of two parent species of chestnut (100% American and 100% Chinese) and three breeding generations (B1 F3, B2 F3, and B3 F2 backcrosses) were planted into loosely graded mine soils with and without tree shelters. First‐year establishment from seeds averaged 81%. After the fourth year, survival without shelters declined for all chestnut stock types except for Chinese (80%): American 40%, B1 F3 70%, B2 F3 40%, and B3 F2 55%. Survival with shelters was only slightly better after the fourth year (average, 60% with shelters and 57% without). Height growth was not different among stock types, and average height after the fourth year was 43 cm without shelters and 56 cm with shelters. In 2009, seeds and seedlings of the same chestnut stock types were planted into brown (pH 4.5) or gray (pH 6.6) mine soils. Only six out of 250 seeds germinated, which was very poor considering 81% average seed germination in 2008. Transplanted chestnut seedling survival was much better. After the third year, seedling survival was 85% in brown and 80% in gray soil, but significant differences were found with stock types. Survival was significantly higher with American, Chinese, and B1 F3 stock types (75%) than with B2 F3 and B3 F2 (60%). Height after the third season averaged 90 cm on brown and 62 cm on gray soil. Chestnut backcrosses displayed no hybrid vigor and were not better in survival and growth than the parent stock. All five stock types grew on mine soils in West Virginia, and we found surface mines to be promising sites for introducing blight‐resistant chestnut backcross trees into the Appalachian forest.